Viability of biocides and consistency of the culture medium on the in vitro establishment of Guadua angustifolia - Oliva-Cruz, Segundo M.; Huaman-Huaman, Eyner; Vilca-Valqui, Nuri C.; Meléndez-Mori, Jegnes B.; Tejada-Alvarado, José J. (BOSQUE, 2022)
The efficient establishment of nodal segments during the micropropagation of Guadua angustifolia is limited by factors such as the high percentage of microbial contamination and necrosis due to the exudation of phenols. Therefore, this study aimed at evaluating the effect of different concentrations of two broad-spectrum biocides (Germon and PPMTM) and the consistency of the culture medium (liquid and semi-solid) on the response to the in vitro establishment of G. angustifolia The experiment was established under a completely randomized design (DCA) with factorial arrangement. Data were subjected to an analysis of variance and Duncan’s test (P ≤ 0.05). Results indicate that the explants treated with 1 mL L-1 of Germon 80 for 10 min had a lower percentage of oxidation, although to reduce microbial contamination it is necessary to increase the disinfection time and the concentration of the disinfectant agent. On the other hand, the addition of 2 mL L-1 of Plant Preservative Mixture (PPMTM) to the culture medium allowed improving the control of endophytic contaminants, favoring the efficient development and elongation of axillary shoots. Regarding the culture media, it can be mentioned that the use of liquid medium generally led to better responses in the in vitro establishment of the explants.